Haqiqah dan Majaz Dalam Kaitannya dengan Ta'wil - Nasir, Abu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
One of the problems in the study of haqiqah and majaz involves the field of language and literature. In the field of Arabic language and literature studies, there is a branch of science, called Balaghoh Science, whose topic of study is haqiqah and majaz as written in this article. Balaghoh science is one of the tools to comprehensively understand the Qur'an, Al-Hadith, Arabic texts or expressions, both from the perspective of lafadz and its meaning. In addition, this science is also closely related to other sciences, including ushul fiqh, tafsir, hadith, tasawwuf, and so on. Understanding haqiqah and majaz is very important in understanding Arabic texts and expressions, especially understanding the Qur'an and Al-Hadith. In Quranic studies, the concepts of haqiqah and majaz are closely related to the issue of ta'wil. Basically, haqiqi expressions do not require ta'wil, while majazi expressions require ta'wil, which is the transfer of outer meaning to inner meaning, namely the meaning behind the apparent, based on rational justifications, taking into account the context and linguistic rules. The writing in this article uses qualitative research methods with a literature study approach. The sources of data for this paper are taken from books, books, and other sources related to the discussion. This article tries to discuss briefly about haqiqah and majaz in relation to ta'wil. Therefore, some of the discussions review: the concept of haqiqah, majaz, and ta'wil; classification of haqiqah; classification of majaz; haqiqah and majaz in the problem of ta'wil; and haqiqah-majaz and ta'wil, between bayani and 'irfani.